2017
DOI: 10.3847/1538-4357/836/1/110
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Contribution of Supernova Explosions to the Chemical Enrichment of Abell 3112 out to R200

Abstract: The spatial distribution of the metals residing in the intra-cluster medium (ICM) of galaxy clusters records all the information on a cluster's nucleosynthesis and chemical enrichment history. We present measurements from a total of 1.2Ms Suzaku XIS and 72ks Chandra observations of the cool-core galaxy cluster Abell 3112 out to its virial radius (∼1470 kpc). We find that the ratio of the observed supernova type Ia explosions to the total supernova explosions has a uniform distribution at a level of 12%-16% o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 53 publications
8
20
0
Order By: Relevance
“…14). Combined with the previous observations of a uniform ∼0.3 Z Fe abundance in the outskirts of (mostly) CC clusters (Fujita et al 2008;Werner et al 2013;Thölken et al 2016;Urban et al 2017;Ezer et al 2017), we conclude that Fe distribution in cluster outskirts of these merging clusters depends very weakly (or not at all) on the dynamical state of the cluster. This has important consequences regarding the chemical history of large-scale structures.…”
Section: Abundance Vs Pseudo-entropy Relationsupporting
confidence: 88%
See 1 more Smart Citation
“…14). Combined with the previous observations of a uniform ∼0.3 Z Fe abundance in the outskirts of (mostly) CC clusters (Fujita et al 2008;Werner et al 2013;Thölken et al 2016;Urban et al 2017;Ezer et al 2017), we conclude that Fe distribution in cluster outskirts of these merging clusters depends very weakly (or not at all) on the dynamical state of the cluster. This has important consequences regarding the chemical history of large-scale structures.…”
Section: Abundance Vs Pseudo-entropy Relationsupporting
confidence: 88%
“…These abundance distributions do not present evidence of evolution up to z ∼ 1 (McDonald et al 2016;Mantz et al 2017;Ettori et al 2017). Moreover, recent X-ray observations with Suzaku (Fujita et al 2008;Werner et al 2013;Urban et al 2017;Ezer et al 2017;Simionescu et al 2017) reveal an uniform radial distribution around ∼0.2-0.3 Z in the outskirts of the galaxy clusters, which suggests an early enrichment of the ICM (i.e. z ∼ 2-3).…”
Section: Introductionmentioning
confidence: 79%
“…Suzaku XIS observations of the Perseus cluster in 78 independent spatial bins and along 8 azimuthal directions revealed a uniform iron abundance of Z Fe = 0.304 ± 0.012 proto-solar, as a function of both azimuth and radius, out to r 200 (Werner et al 2013). Very deep Suzaku observations of Abell 3112 (Ezer et al 2017) as well as the analysis of archival Suzaku data for the outskirts of ten massive clusters ) confirm the results of the Perseus observations. find that, across their sample, the Fe abundances are consistent with a constant value, Z Fe = 0.306 ± 0.012 proto-solar, which is remarkably similar to the value measured for the Perseus cluster.…”
Section: Metals In Cluster Outskirtssupporting
confidence: 73%
“…From the same respective studies, the red circles and the red shaded area show the intrinsic scatter of the measurements (following the method of ). The black dotted line, the yellow triangles, the green squares, and the black stars show respectively the Suzaku XIS measurements of the outskirts of the Perseus cluster (Werner et al 2013, averaged value), the UGC 03957 group (Thölken et al 2016), the A 3112 cluster (Ezer et al 2017), and the Virgo cluster , azimuthally averaged along the N, S, and W arms). All the abundances are rescaled with respect to the proto-solar values of Lodders et al (2009). Rgs Sample (CHEERS), including clusters, groups, and massive ellipiticals -and showed that their azimuthally averaged SNIa-to-SNcc contribution remains remarkably uniform out to at least ∼0.5 r 500 .…”
Section: Central Abundance Distributionmentioning
confidence: 99%
“…Beyond that radius, the metallicity is consistent with being flat, as shown by the measurements of the ICM metallicity up to the virial radius for several clusters (e.g. Fujita et al 2008, Werner et al 2013, Simionescu et al 2015, Thölken et al 2016, Ezer et al 2017, Urban et al 2017.…”
Section: Introductionsupporting
confidence: 68%